KARAKTERISASI Neisseria gonorrhoeae PADA KELOMPOK RESIKO TINGGI DI KOTA JAYAPURA DENGAN PENDEKATAN FENETIK - Yunus Kulle; Dirk Y.P. Runtuboi (NOVAE GUINEA Jurnal Biologi, 2015)
AbstractÂ Gonorrhea is a sexually transmitted infection caused by N. gonorrhoeae, with prevalence for the city of Jayapura in 2011 amounted to 32.4%. Character of the data required for the evaluation and development of diagnostic methods. This study aims to determine the presence of bacteria N. gonorrhoeae isolates and clinical phenotypic characters of high-risk groups in the city of Jayapura. This type of research is descriptive research with a laboratory experimental research design using cross-sectional methods. Research carried out by isolation, selection and identification and analysis of phenotypic characters. Phenotypic characters were analyzed as many as 84 characters. Results of isolation, selection and identification of 50 clinical isolates sampled high-risk groups Jayapura city region showed that 8 isolates (16%) were positive N.gonorrhoeae were divided into 2 clusters. Simple Matching similarity index value of coeficient (SSM) for 8 isolates the test more than 90%. Key Words: Characterization, Neisseria gonorrhoeae, Fenetic